1995
DOI: 10.1149/1.2049973
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Chemistry of Rechargeable Li /  SO 2 Cells Containing Tetrachlorometallate:  SO 2 Electrolytes

Abstract: The chemistry of the rechargeable system Li/LiA1CI~ 9 x SQ/C (where x = 2.8 to 6), which has an open-circuit voltage of 3.2 V, was investigated and compared with that of Li/LiGaC14 -xSO2/C, which has an open-circuit voltage of 2.9 V. Cyclic voltammetry, pressure measurements, elemental analysis, and vibrational spectroscopy were used to monitor the cycling behavior and the nature of the discharge products. For the LiA]C14 based electrolyte, the discharge products were LiC1 and an amorphous complex believed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…1a), the discharge capacity of a Li-SO 2 cell is highly dependent on the type of carbon material used. Given that the underlying reaction mechanism in a Li-SO 2 system is the redox reaction of sulfur species from +4 to +3, thereby producing solid phases of LiCl and LiAlCl(SO 2 ) 3 on the surface of the carbon cathode, 13 it is not surprising that carbon materials with higher specific area allow a higher discharge capacity. To elucidate the correlation of the discharge capacity with various carbon properties, we quantitatively determined the specific surface area, pore size, and pore volume of the above-listed five different carbon materials using N 2 sorption-desorption isotherms (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a), the discharge capacity of a Li-SO 2 cell is highly dependent on the type of carbon material used. Given that the underlying reaction mechanism in a Li-SO 2 system is the redox reaction of sulfur species from +4 to +3, thereby producing solid phases of LiCl and LiAlCl(SO 2 ) 3 on the surface of the carbon cathode, 13 it is not surprising that carbon materials with higher specific area allow a higher discharge capacity. To elucidate the correlation of the discharge capacity with various carbon properties, we quantitatively determined the specific surface area, pore size, and pore volume of the above-listed five different carbon materials using N 2 sorption-desorption isotherms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 Although the theoretical capacity of the SO 2 based catholyte (219 mA h g À1 and 372 mA h cm À3 , based on the mass and volume of LiAlCl 4 Á3SO 2 , respectively) is lower than that observed in the case of Li-O 2 and Li-S batteries, we found that the theoretical energy density of the rechargeable Li-SO 2 battery system (651 W h kg À1 ) is 68% higher than that of the conventional LIBs (387 W h kg À1 ). 13 As already mentioned, recent achievements in materials science and nanotechnology have greatly enhanced the electrochemical performance of post-LIBs. From these results, we expect that the performance of the Li-SO 2 battery can be also significantly improved, if recently discovered nanostructured materials are appropriately exploited in the system.…”
Section: Broader Contextmentioning
confidence: 97%
“…− radical anions which displace Cl − from AlCl 4 − to form NaCl. In a Li–SO 2 battery, homologue of Na–SO 2 , LiCl and LiAlCl(SO 2 ) 3 have been considered as discharge products13: 3 moles of reduced SO 2 .− anions react with 1 mole of AlCl 4 − sequentially, thereby forming insoluble 3 moles of LiCl and 1 mole of LiAlCl(SO 2 ) 3 , which precipitate at the carbon cathode. While LiCl was confirmed by XRD analysis, the SO 2 -substituted second form of the discharge product has not been identified clearly despite several efforts made in various experimental analyses13.…”
Section: Resultsmentioning
confidence: 99%
“…Primary Li–SO 2 batteries in which liquefied SO 2 serves as the active cathode material have been commercialized for military and industrial applications910, and ongoing interest for further development is still found11. About 30 years ago, there were also intensive studies on Li–SO 2 rechargeable batteries based on a LiAlCl 4 ⋅ x SO 2 inorganic molten complex catholyte, which shows completely different reaction chemistry from the primary SO 2 battery81213141516. Rechargeable Li–SO 2 battery showed a discharge capacity of ~1000 mAh g −1 based on the carbon electrode (theoretical catholyte capacity of 144 mAh g −1 for LiAlCl 4 ⋅6SO 2 ) with an operating voltage of 3.2 V, and Duracell demonstrated the performance of prototype C-size Li–SO 2 rechargeable batteries12.…”
mentioning
confidence: 99%
See 1 more Smart Citation